Auditoría de gestión al departamento de compras públicas de la Universidad Estatal Amazónica del cantón Pastaza, período 2017 - Aguayo Ibarra, Ligia Zaida (2018)
In the present investigation, the Public Procurement Department of the Amazon State University (UEA) in the Province of Pastaza has been reviewed and evaluated, based on the research objective that was: to evaluate the processes that are executed in the public procurement activity. This department has the purpose of satisfying the needs of goods and services, which are required to fulfill the objectives that have been proposed as an institution. It was decided to implement a management audit in order to identify the legal shortcomings that lead to commit administrative errors that may affect the officials responsible for the execution of expenditure, as well as those who perform the control and found not to have a institutional regulation and a manual of functions with regard to your organization. The study was carried out using the instrument of the interview to the Coordinator of the department, which allowed gathering truthful and verifiable information. The results obtained, allowed to know that there are legal gaps in the process of acquisition of goods and services, few timely requirements of the different departmental units and processes with very small amount that were detected by the SERCOP portal. Keywords: Management Audit, public purchases, public management.